2020
DOI: 10.1126/sciadv.aax9976
|View full text |Cite
|
Sign up to set email alerts
|

π-π stacking interactions: Non-negligible forces for stabilizing porous supramolecular frameworks

Abstract: Revealing the contribution of - stacking interactions in supramolecular assembly is important for understanding the intrinsic nature of molecular assembly fundamentally. However, because they are much weaker than covalent bonds, - stacking interactions are usually ignored in the construction of porous materials. Obtaining stable porous materials that are only dependent on - stacking interactions, despite being very challenging, could address this concern. Here, we present a porous supramolecular framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
203
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(208 citation statements)
references
References 57 publications
5
203
0
Order By: Relevance
“…However, controlled large-scale assembly is one of the more crucial aspects for effective charge transport in organic semiconductors and is difficult to achieve. The emergence of organic frameworks (OFs) has opened an avenue for predicting and controlling the molecular assembly, especially in covalent OFs (COFs) (14)(15)(16)(17). The final COF topology can now be determined based on the relative geometries of raw materials.…”
mentioning
confidence: 99%
“…However, controlled large-scale assembly is one of the more crucial aspects for effective charge transport in organic semiconductors and is difficult to achieve. The emergence of organic frameworks (OFs) has opened an avenue for predicting and controlling the molecular assembly, especially in covalent OFs (COFs) (14)(15)(16)(17). The final COF topology can now be determined based on the relative geometries of raw materials.…”
mentioning
confidence: 99%
“…Previous studies have shown that π-π stacking interactions predominate for the structural stability in porous materials such as metal organic frameworks (MOFs) and hydrogen-bonded organic framework (HOFs). [32][33][34] In comparison with COF-HNU7, two types of π-π stacking modes were observed in the large πconjugated system of COF-HNU6 (Figure 5b), including the π-π interactions between building blocks along the c-axis (interlayer distance 3.479 Å) and the strong π-π interactions between azobenzene rings along the c-axis (interlayer distance 3.479 Å). It was found that the interlayer interaction energy dramatically increased from 60.88 kcal mol À 1 for COF-HNU7 to 91.4 kcal mol À 1 for COF-HNU6 due to the incorporating azobenzene groups (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The interactions in Table 2 consisted of two hydrophilic hydrogen bonding with two ASN-343 and one strong hydrophobic π-π stacking interaction with TRP-436 amino acid. The π-π stacking interaction can significantly increase ligand-protein stability [60] which would mean the structural and functional properties of meloxicam would remain unaltered during drug delivery thus increasing therapeutic efficacy [61]. The interactions of meloxicam were weaker with the 6LU7 protein which consisted of one hydrogen hydrophilic interaction with ASP-153 and one hydrophobic pi-H interaction with TYR-154 amino acid.…”
Section: Meloxicammentioning
confidence: 99%